Promoting Functional Activity Engagement in People with Multiple Disabilities through the Use of Microswitch-Aided Programs - Lancioni, Giulio E.; Singh, Nirbhay N.; O’Reilly, Mark F.; Sigafoos, Jeff; Alberti, Gloria; Perilli, Viviana; Campodonico, Francesca (Frontiers in Public Health, 2017)
Background: People with severe/profound multiple (e.g., intellectual, motor, or sensory-motor) disabilities are frequently restricted to a situation of inactivity and dependence, which may be modified by promoting functional activity engagement through assistive technology. Methods: This study assessed the possibility of promoting functional activity engagement via microswitch-aided programs with nine participants with multiple disabilities between 10 and 29 years of age. Functional activity consisted of constructive interaction with the immediate environment (e.g., reaching/touching or putting away objects) through the use of response schemes considered practical and beneficial for the participants’ physical exercise and general condition. Microswitch-aided programs were used to monitor the participants’ responses and to automatically provide stimulation opportunities contingent on those responses. Results. All participants had a large/significant increase in their activity engagement (i.e., response frequencies) during the microswitch-aided programs, compared to the baseline periods. These data, which are in line with previous findings in the area, indicate that the programs targeted activity and responses suitable for the participants and ensured contingent stimulation effective to motivate them. Conclusions. People with severe/profound multiple disabilities can engage in functional activity with the help of microswitch-aided programs.